Black Cuban, Black American : a memoir - Grillo, Evelio (Hispanic civil rights series., 2000)
Growing up in Ybor City (now Tampa) in the early twentieth century, the young Evelio Grillo experienced the complexities of life in a horse-and-buggy society demarcated by both racial and linguistic lines: Life was different depending on whether one was Spanish- or English- speaking, a white or black Cuban, a Cuban American or a native-born U.S. citizen, well-off or poor. (Even American-born blacks did not always get along with their Hispanic counterparts.)".